A Comprehensive Performance Comparison of DFT-S DMT and QAM-DMT in UOWC System in Different Water Environments - Ji Du; Xiaojian Hong; Yuan Wang; Zhanpeng Xu; Wenyi Zhao; Nanfei Lv; Chao Fei; Sailing He (IEEE Photonics Journal)
In this paper, we experimentally demonstrate a 450-nm laser underwater optical wireless transmission system, in which a comprehensive investigation is made to show the significant performance improvement of the discrete Fourier transform spread discrete multi-tone (DFT-S DMT) as compared to the conventional quadrature amplitude modulation discrete multi-tone (QAM-DMT) modulation. DFT-S DMT outperforms QAM-DMT in terms of bit error rate (BER) performance due to low peak-to-average-power ratio (PAPR) and capability of counteracting high frequency fading in a band-limited underwater optical wireless communication (UOWC) system. In order to avoid signal-to-noise-ratio (SNR) degradation at fringe subcarriers, several zeros are padded at the edge of each block before DFT-S operation. The experimental results show the superiority of DFT-S DMT compared with QAM-DMT in different water environments, including turbidities, bubbles, and water flow. Data rates of ∼16.16 Gbps and ∼13.96 Gbps at a BER of 3.8 × 10−3 are achieved by 16-QAM DFT-S DMT and 16-QAM-DMT over a 5-m water channel, respectively, which indicates that capacity enhancement of ∼2.2 Gbps is obtained by the DFT-S DMT. Meanwhile, over 3-dB receiver sensitivity improvement can always be achieved by the DFT-S DMT at the tested underwater transmission distances. Combined with adaptive bit-power loading, 20.04 Gbps over a 5-m “clear ocean” channel transmission with a single laser diode (LD) is demonstrated. For a 35-m water link, the distance-data rate product reaches 498.4 Gbps*m. To the best of our knowledge, both the data rate and distance-data rate product are the largest among all the results reported for a single visible LD. Aimed at high-speed deep ocean applications, the studies are promising for future UOWC research.